PENGEMBANGAN PRODUKSI SORGUM DI LAHAN RAWA: KAJIAN PEMANFAATAN ALELOPATI SEBAGAI BIOHERBISIDA - Edi Susilo; Fahrurrozi Fahrurrozi; Sumardi Sumardi (University of Prof. Dr. Hazairin, SH, 2020)
Efforts to fulfill food demands for Indonesian to comply with population increases endorse to extend production areas to marginal lands. Sorghum which has an ability to adapt with less favourable growing environments almost has nutritional values as good as corn, but this crop is less cultivated by farmers. Adaptation mechanisms of sorghum to environmental stresses are by producing natural allelopathies. Those allelochemicals could be properly managed as natural herbicides for sorghum production in swamplands. This review aimed to describe the potential uses of allelochemicals produced by sorghum for sustainable sorghum production in swamplands. Reviews concluded that (1) sorghum is most likely suitable for swamplands due to its wide range abilities to cope biotic and abiotic stressors, (2) sorghum is able to increase the production of sorgoleone, dhurrin and phenolic allelochemicals, and (3) those allelochemical extracts could be developed as bioherbicide compounds for sustainable production of various crops.